Mechanical compression during repeated sustained isometric muscle contractions and hyperemic recovery in healthy young males - Osada, Takuya; Mortensen, Stefan P.; Rådegran, Göran (Journal of physiological anthropology, 2015)
An elevated intramuscular pressure during a single forearm isometric muscle contraction may restrict muscle hyperemia. However, during repeated isometric exercise, it is unclear to what extent mechanical compression and muscle vasodilatation contribute to the magnitude and time course of beat-to-beat limb hemodynamics, due to alterations in leg vascular conductance (LVC). In eight healthy male subjects, the time course of both beat-to-beat leg blood flow (LBF) and LVC in the femoral artery was determined between repeated 10-s isometric thigh muscle contractions and 10-s muscle relaxation (a duty cycle of 20 s) for steady-state 120 s at five target workloads (10, 30, 50, 70, and 90% of maximum voluntary contraction (MVC)). The ratio of restricted LBF due to mechanical compression across workloads was determined by the formula (relaxation LBF--contraction LBF)/relaxation LBF (%). The exercise protocol was performed completely by all subjects (≤ 50% MVC), seven subjects (≤ 70% MVC), and two subjects (≤ 90% MVC). During a 10-s isometric muscle contraction, the time course in both beat-to-beat LBF and LVC displayed a fitting curve with an exponential increase (P < 0.001, r (2) ≥ 0.956) at each workload but no significant difference in mean LBF across workloads and pre-exercise. During a 10-s muscle relaxation, the time course in both beat-to-beat LBF and LVC increased as a function of workload, followed by a linear decline (P < 0.001, r (2) ≥ 0.889), that was workload-dependent, resulting in mean LBF increasing linearly across workloads (P < 0.01, r (2) = 0.984). The ratio of restricted LBF can be described as a single exponential decay with an increase in workload, which has inflection point distinctions between 30 and 50% MVC. In a 20-s duty cycle of steady-state repeated isometric muscle contractions, the post-contraction hyperemia (magnitude of both LBF and LVC) during muscle relaxation was in proportion to the workload, which is in agreement with previous findings. Furthermore, time-dependent beat-to-beat muscle vasodilatation was seen, but not restricted, during isometric muscle contractions through all target workloads. Additionally, the relative contribution of mechanical obstruction and vasodilatation to the hyperemia observed in the repeated isometric exercise protocol was non-linear with regard to workload. In combination with repeated isometric exercise, the findings could potentially prove to be useful indicators of circulatory adjustment by mechanical compression for muscle-related disease.